Implementation And Governance of The Free Nutritious Meal Program as a Public Service Policy in North Sulawesi Province - Devie Seem Rony Siwij; Margareta Oktavia Sumilat (Journal of Governance, 2026)
This study aims to analyze the implementation and governance of the Free Nutritious Meal Program (MBG) as a public service policy in North Sulawesi Province. The MBG program is a strategic social policy aimed at improving students' nutritional well-being and strengthening local governments' role in providing basic public services. Given the region's diverse geographic and social characteristics, evaluating policy implementation is important for assessing the effectiveness of local government programs. This study uses a quantitative approach based on the Importance-Performance Analysis (IPA) method. Data were collected through a questionnaire completed by 420 respondents, including school principals, teachers, and program managers, across 15 districts/cities. The study's results indicate that all MBG Program indicators are highly important; however, performance gaps exist in distribution timeliness, menu variety, and suitability for local tastes. These findings confirm that the effectiveness of the MBG Program is greatly influenced by the quality of policy implementation and cross-sectoral governance at the regional level.